2005
DOI: 10.1115/1.1805550
|View full text |Cite
|
Sign up to set email alerts
|

Laser Ignition of Methane-Air Mixtures at High Pressures and Diagnostics

Abstract: Methane-air mixtures at high fill pressures up to 30 bar and high temperatures up to 200°C were ignited in a high-pressure chamber with automated fill control by a 5 ns pulsed Nd:YAG laser at 1064 nm wavelength. Both, the minimum input laser pulse energy for ignition and the transmitted fraction of energy through the generated plasma were measured as a function of the air/fuel-equivalence ratio (λ). The lean-side ignition limit of methane-air mixtures was found to be λ=2.2. However, only λ<2.1 seems to be p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…However, Kopecek et al (2003) investigated the effect of laser pulse energy in methane-air mixtures and concluded that shorter combustion durations and higher peak pressures can be achieved with increased laser pulse energy, which was also observed by Morsy and Chung (2003). Fuel-air mixtures were also ignited using a spark plug under identical experimental conditions, and results were compared with those of laser ignition by several researchers; they found that laser ignition led to shorter ignition delay and shorter combustion duration compared with conventional spark ignition (Ma et al, 1998;Kopecek et al, 2005). Pressure history of hydrogen-air mixtures in the combustion chamber for single, two, and three point ignition was experimentally investigated by Morsy and Chung (2003) and Morsy (2012), and it was concluded that significant enhancement of the combustion process, especially in lean mixtures, could be achieved through the use of the most incident laser energy achieved by laser-induced cavity ignition, by simultaneous initiation of combustion at multiple locations, or through increasing the turbulence caused by ignition.…”
Section: Introductionmentioning
confidence: 91%
“…However, Kopecek et al (2003) investigated the effect of laser pulse energy in methane-air mixtures and concluded that shorter combustion durations and higher peak pressures can be achieved with increased laser pulse energy, which was also observed by Morsy and Chung (2003). Fuel-air mixtures were also ignited using a spark plug under identical experimental conditions, and results were compared with those of laser ignition by several researchers; they found that laser ignition led to shorter ignition delay and shorter combustion duration compared with conventional spark ignition (Ma et al, 1998;Kopecek et al, 2005). Pressure history of hydrogen-air mixtures in the combustion chamber for single, two, and three point ignition was experimentally investigated by Morsy and Chung (2003) and Morsy (2012), and it was concluded that significant enhancement of the combustion process, especially in lean mixtures, could be achieved through the use of the most incident laser energy achieved by laser-induced cavity ignition, by simultaneous initiation of combustion at multiple locations, or through increasing the turbulence caused by ignition.…”
Section: Introductionmentioning
confidence: 91%
“…Minimum ignition energy (MIE) has been identified as an important parameter for ignition studies, which has a great dependence on mixture fraction and flow conditions around the ignition point. The influence of the mixture fraction on MIE has been studied extensively both in quiescent conditions [8][9][10] and laminar premixed flows [11,12]. The MIE was found to be the lowest at mixture fractions near stoichiometric and increase towards the lean and rich sides of stoichiometry.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are several alternative ignition concepts for example plasma ignition, high-frequency ignition, Diesel micro-pilot ignition and * E-mail: johannes.tauer@tuwien.ac.at laser ignition which may contribute to an improvement of the overall engine efficiency. To our knowledge, laser ignition represents the most promising future ignition concept for a number of reasons [1][2][3][4]. The main advantages of laser ignition, among many others, are performance enhancing high effective mean pressures in the combustion chamber as well as the feasibility of very lean mixtures lowering the flame temperature and consequently the NO emissions.…”
Section: Introductionmentioning
confidence: 99%